779. Clostridiodes difficile: Is it time for surveillance! Cost-benefit analysis. (31st December 2020) - Yassin, Mohamed; Donskey, Curtis; Arbulu, Ricardo; Dixon, Heather; Smith, Kenneth
Abstract: Background: Clostridiodes difficile infection (CDI) has substantial morbidity, mortality and expense. Hospital surveillance to detect CD carriers could affect antibiotic use and determination of community-associated vs hospital-associated CDI. Methods: A decision tree examined the cost-effectiveness of hospital CD surveillance compared to current practice (testing as indicated). Costs for CD testing, community-associated CDI and hospital-associated CDI came from US databases. CD carrier and infection probabilities came from literature and local data. Analyses examined potential benefits from 1) knowledge of CD carrier status affecting antibiotic use (healthcare perspective) and 2) avoiding penalties for hospital-acquired CDI (hospital perspective). Results: From the healthcare perspective, if antibiotic use is unchanged by CD status, surveillance costs $39/patient than current practice with unchanged CDI risk. However, if knowing CD status changed antibiotic prescribing such that CDI risk decreased by 10% or 20%, then cost/CDI avoided becomes $15, 519 and $3, 822 respectively, with CD surveillance becoming cheaper and more effective current practice if CDI risk decreased ≥30%. From the hospital perspective, using published CDI incidence (2.7%) and a hospital-associated CDI penalty of $30, 000, surveillance cost $336/patient less than current practice if patients colonized on admission were not considered hospital-associated CDI and $476/patient less with local data (incidence 4.2%). Conclusion: Hospital CD surveillance is potentially a cost-effective or cost-saving strategy depending on perspective taken and clinical usage of these data. This strategy could be implemented hospital-wide or in high-risk populations. CD surveillance could be both cost-saving and decrease CDI risk if more appropriate antibiotic use results from its use. Disclosures: All Authors : No reported disclosures